The Readiness of The Young Generation to Invest - Nugroho, Jovita Antania; Usman, Usman (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to determine the readiness of young generation to invest by exploring the relationship between financial literacy, risk attitude, and the role of social media in investment decision-making. The research utilized a quantitative approach and involved 207 young generation from Semarang who had either never invested or were previously invested. Data were collected using a questionnaire and analyzed with PLS-SEM. The results show that young generation who have never invested perceive social media as enhancing financial literacy, affecting their risk attitude and investment behavior. In contrast, those with prior experience find social media content irrelevant, their financial literacy directly influences their risk attitude and investment behavior. Demographic factors do not moderate the relationship between social media and financial literacy for either group. The study emphasizes strong financial literacy and better-quality investment content on social media to support informed decisions among youth.